Effects of substrate termination on Ron increase under stress in 650 V GaN power devices. (23rd April 2021) - Li, Feiyu; Wang, Ronghua; Huang, Huolin; Ren, Yongshuo; Ren, Guangshan; Liang, Zhuang; Zhou, Fubin; Cheng, Wanxi; Liang, Huinan
Abstract: Buffer related electron trapping and hot electron injection are responsible for R on degradation in devices, but the effects of substrate termination are still uncertain. In this work, both positive and negative substrate bias are applied to investigate the different vertical trapping mechanisms in 650 V gallium nitride (GaN) power devices. R on shows an instant and significant increase under vertical bias stress, and the magnitude of downward buffer electron trapping induced R on increase is relatively larger than that induced by upward trapping. Additionally, the substrate floated and grounded GaN devices are also submitted to both off-state and semi-on-state stresses to investigate the effects of substrate termination on hot electron injection induced R on increase. The intensity of the upward electron trapping increases faster with temperature resulting in a higher R on increase than the downward situation. The hot electron effect is only obvious when the substrate is grounded, suggesting that the main injection destination is not in the buffer. The substrate floated device exhibits a lower R on increase after both off-state and semi-on-state stresses at elevated temperatures. Substrate floated packages are suggested to ensure reliable dynamic performance of device, especially for high voltage application design.